George Washington Campbell papers - Campbell, George Washington, 1769-1848.
Correspondence, diaries, reports, drafts, and letterbook relating chiefly to Campbell's service as U.S. senator, secretary of the treasury under James Madison, and minister to Russia (1818-1820). Includes correspondence with Richard Rush in London while minister to Russia and Campbell's report to the Dept. of State while commissioner under the Convention of 1831 with France; papers of Campbell's sons-in-law, David Hubbard and Richard Stoddert Ewell, reflecting Alabama and national politics prior to the Civil War and relating to military affairs; and correspondence and diary (1864-1869) of Major Campbell Brown, a stepson of General Ewell. Correspondents include John C. Calhoun, Edmund Pendleton Gaines, David Hubbard, Andrew Jackson, Robert E. Lee, James Madison, and Richard Rush.
In part, photocopies.
U.S. representative from Tennessee, secretary of the treasury, lawyer, and diplomat.
Collection material in English.
Keywords: Brown, Campbell, -- 1840-1893.; Calhoun, John C. -- 1782-1850 -- Correspondence; Ewell, Richard Stoddert, -- 1817-1872.; Gaines, Edmund Pendleton, -- 1777-1849 -- Correspondence; Hubbard, David, -- 1792-1874 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Madison, James, -- 1751-1836.; Madison, James, -- 1751-1836 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; United States. -- Department of State; Diplomatic and consular service, American -- France; Diplomatic and consular service, American -- Russia; Alabama -- Politics and government -- To 1865.; France -- Foreign relations -- United States; Russia -- Foreign relations -- United States; United States -- Foreign relations -- 1815-1861.; United States -- Foreign relations -- France; United States -- Foreign relations -- Russia; United States -- Politics and government -- 1783-1865.; Cabinet officers; Diplomats; Lawyers; Senators, U.S. Congress -- Tennessee